ORGANIC FARMING TECHNOLOGY OF UTILIZING OIL PALM EMPTY FRUIT BUNCH COMPOST AND LEGUMINOSAE PLANT COMPOST TO REDUCE NPK FERTILIZER DOSAGE ON GROWTH AND YIELD OF BROWN RICE (ORYZA NIVARA) - Fitriana M.; Sulaiman F.; Sodikin E. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This research was aimed to evaluate the effect of organic and inorganic fertilizer combinations on growth and yield of brown rice (Oryza nivara L). The research was conducted from July to November 2018 in experimental farm of Faculty of Agriculture, Sriwijaya University. The method used in this research was randomized block design with seven treatments and three replications. Treatments given were 100% urea fertilizer, SP-36, KCl (P1); stringbean compost + 25% urea, SP-36, KCl (P2); stringbean compost + 50% urea, SP-36, KCl (P3); oil palm empty fruit bunch compost + 25% urea, SP- 36, KCl (P4); oil palm fruit bunch compost + 50% urea, SP-36, KCl (P5); chicken manure fertilizer + 25% urea, SP-36, KCl (P6); and chicken manure fertilizer + 50% urea, SP-36, KCl (P7). Research result showed that the combination of organic and inorganic fertilizer gave better result compared to solely organic or inorganic fertilizer. Treatment with the best result for the growth and yield of brown rice was treatment P5 (oil palm empty fruit bunch compost + 50% N,P,K fertilizer), followed by P7 (manure fertilizer + 50% NPK fertilizer). The highest yield per hectare was treatment P5 with 5,49 tonnes.